Tetraspanin Assemblies in Virus Infection - Florin, Luise; Lang, Thorsten (Frontiers in Immunology, 2018)
Tetraspanins are a family of four-span transmembrane proteins, known as plasma membrane ‘master organizers’. They form tetraspanin-enriched microdomains (TEMs or TERMs) through lateral association with one another and other membrane proteins. If multiple microdomains associate with each other, larger platforms can form. For infection, viruses interact with multiple cell surface components including receptors, activating proteases, and signaling molecules. It appears that tetraspanins such as CD151, CD82, CD81, CD63, CD9, Tspan9, and Tspan7 coordinate these associations by concentrating the interacting partners into tetraspanin platforms. In addition to mediating viral attachment and entry, these platforms may also be involved in intracellular trafficking of internalized viruses and assist in defining virus assembly and exit sites. In conclusion, tetraspanins play a role in viral infection at different stages of the virus replication cycle. The present review highlights recently published data on this topic, with a focus on events at the plasma membrane. In light of these findings, we propose a model for how tetraspanin interactions may organize cofactors for viral infection into distinct molecular platforms.